Mitral valve prolapse: American versus European guidelines - which one is better. (8th February 2021) - Brito, J; Rigueira, J; Rodrigues, T; Aguiar-Ricardo, I; Santos, R; Nunes-Ferreira, A; Cunha, N; Pereira, S; Antonio, PS; Morais, P; Alves Silva, P; Valente Silva, B; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: According to the most recent recommendations of AHA, mitral valve prolapse (MVP) is defined as systolic displacement of the mitral leaflet into the left atrium (LA) of at least 2 mm from the mitral annular plane. The ESC recommendations define MVP, flail and billowing, according to the location of the leaflet tips in relation to the coaptation plan. Differences in outcomes considering these classifications are not established. Purpose: To evaluate the differences in clinical presentation and outcomes of MVP considering AHA and ESC classifications. Methods: Single-center retrospective study of consecutive patients with MVP (defined according to the AHA classification) documented in transthoracic echocardiogram between January 2014 and October 2019. Demographic, clinical, echocardiographic and electrocardiographic data were collected. The results were obtained using Chi-square and ANOVA tests. Results: We included 247 patients (mean age 62.9 ± 18 years, 61% males) according to AHA classification; considering the ESC classification: 147 (59%) had prolapse, 30 (12%) flail and 67 (39%) billowing. In comparison to patients with flail and billowing, patients with MVP had less cordae rupture (p = 0.02). Prolapse was associated with better survival (p = 0.037) and was an independent predictor of survival (OR = 0.372, CI95% [0.148-0.935], p = 0.035) Patients with flail were older in comparison to the ones with prolapse and billowing (71 ± 14 vs 63 ± 17 vs 60 ± 21 years, respectively, p = 0.022). Patients with flail were mostly men (80%, p = 0.028), with more significant mitral regurgitation (p = 0.003) and higher NYHA class (p = 0.018). They also had higher systolic pulmonary artery pressure (SPAP) (48 ± 23 vs 38 ± 18 vs 36 ± 12mmHg, p = 0.015) and higher values of LV mass and posterior wall thickness (144 ±32 vs 125 ± 44 vs 114 ± 37g/m2, p = 0.005 and 11 ± 1, 5 vs 10 ± 1, 7 vs 9 ± 1.9 mm, p = 0.009, respectively). Women had more billowing (p = 0.04) than prolapse and flail. Conclusion: The ESC classification adds information to the AHA classification in what concerns to clinical presentation and prognosis of mitral valve prolapse, so both classifications should be used in daily practice.